Targeting Growth Factor Receptors in Cancer Insights from Molecular Docking Studies: A Literature Review - Imelda Maelani; Widya Syahfitri; Fitri Elizabrth Hasibuan2 Hasibuan (Universitas Syiah Kuala, 2025)
Growth factor receptors (GFRs) are essential transmembrane proteins that regulate key cellular processes such as proliferation, differentiation, migration, and survival. Their aberrant activation is strongly linked to cancer initiation, progression, and therapeutic resistance. Although several studies have explored GFR inhibition experimentally, the integration of in silico approaches remains underdeveloped. This review critically examines recent applications of molecular docking in identifying and characterizing inhibitors targeting major GFR families, including EGFRs, IGFRs, VEGFRs, TGF-βRs, FGFRs, and PDGFRs. A systematic literature search was conducted across major databases to summarize ligand–receptor interactions and binding mechanisms reported between 2004 and 2024. The analysis reveals that molecular docking effectively predicts ligand affinity and receptor selectivity, enabling the identification of natural and synthetic compounds with potent inhibitory potential. Moreover, patterns across docking studies indicate distinct binding preferences among receptor subtypes, providing valuable insights for structure-based drug design. Despite its predictive power, limitations such as receptor rigidity and lack of biological context highlight the need for integration with dynamic simulations and experimental validation. Overall, this review underscores the promise of docking-based screening as a strategic tool for accelerating the discovery of selective and safer anticancer agents targeting GFRs.